PEREMPUAN DAN ADAT PERKAWINAN (STUDI TENTANG MARGINALISASI PEREMPUAN DALAM JUJURAN ADAT ISTIADAT PERKAWINAN DI NIAS) - Efentinus Ndruru (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
The study of gender studies (gender mainstreaming) today is a response to the phenomenon of domestic violence. Violence is inseparable from the dominance of men who are constructed in patriarchal culture. Women's research and marriage customs that impact on the marginalization of women in Nias is a continuous series of critics for gender observers, especially in the practice of marriage customs. There is a tendency of